Analisis Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama - Muhamad Mas'ud (STES Islamic Village, 2021)
The settlement of Islamic economy disputes has become a new challenge for the Religious Court since the enactment of Law no. 3 of 2006 in conjunction with Law Number 50 of 2009. By regulation, the settlement of Islamic economy disputes in the Religious Courts becomes a trust for the Religious Court which are under the Supreme Court. This study aims to review the settlement of Islamic economy disputes in the Religious Court which is the absolute authority in receiving, examining, and deciding cases, especially in Islamic economy disputes. Descriptive qualitative method is the choice in this study on the regulation of the Law on the Judicial Power. Religious Court in carrying out their absolute competence based on the regulations of Law No. 3 of 2006 and Law no. 50 of 2009 have fulfilled the aspect of justice for disputes, especially in handling and deciding Islamic economy disputes. This is based on the number of cases in the Religious Court that have been successfully decided and have progressed, although some of the justice seekers have filed appeals and cassation. This shows that the Religious Court is competent in responding to challenges and doubts in resolving sharia economy disputes.Keywords: Islamic Economics; Religious Court; Dispute; Islamic LawPenyelesaian sengketa ekonomi syari’ah menjadi sebuah tantangan baru bagi Pengadilan Agama semenjak diberlakukannya UU No. 3 Tahun 2006 Jo UU Nomor 50 Tahun 2009. Secara regulasi penyelesaian sengketa ekonomi syari’ah di Pengadilan Agama menjadi sebuah trust terhadap Pengadilan Agama yang berada dibawah Mahkamah Agung. Penelitian ini bertujuan untuk melihat penyelesaian sengketa ekonomi syari’ah di Pengadilan Agama yang menjadi kewenangan absolut dalam menerima, memeriksa, dan memutus perkara khususnya dalam sengketa ekonomi syari’ah. Metode kualitatif deskriptif menjadi pilihan dalam penelitian ini terhadap regulasi Undang-undang Kekuasaan Kehakiman. Pengadilan Agama dalam menjalankan kompetensi absolutnya berdasarkan regulasi Undang-undang No.3 Tahun 2006 dan Undang-undang No. 50 Tahun 2009 telah memnuhi aspek keadilan bagi para sengketa khususnya dalam menangani dan memutus sengketa ekonomi syari’ah. Hal ini berdasarkan dengan jumlah perkara di Pengadilan Agama yang berhasil diputus dan telah incraht meskipun sebagian dari pencari keadilan mengajukan banding dan kasasi. Hal ini menunjukan bahwa badan Peradilan Agama telah kompeten dalam menjawab sebuah tantangan dan keraguan dalam menyelesaian sengketa ekonomi syari’ah. Keywords: Ekonomi Syari’ah; Peradilan Agama; Penyelesaian Sengketa; Hukum Islam